FENOMENA LIVE TIKTOK SEBAGAI MEDIA MENGEMIS ONLINE PERSPEKTIF ETIKA SOSIAL AL-QUR’AN - Siti Nur Azizah; Safiin Mansur (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The phenomenon of live streaming on TikTok has given rise to a new practice called online begging or cyber begging, where individuals display actions that evoke sympathy in order to receive digital gifts from viewers. This study aims to analyze this phenomenon through the perspective of social ethics in the Qur’an, particularly the values of iffah (maintaining one’s dignity), ‘adl (justice), ihsan (kindness), and ta‘awun (mutual assistance). The study employs a descriptive qualitative method with a Qur’anic social ethics approach, using digital observation and semi-structured interviews with TikTok users, as well as analysis of classical and contemporary interpretations. The results of the study indicate that the practice of online begging represents a form of moral degradation caused by the shift in social values from honor and hard work towards fame and material gain. This phenomenon contradicts the principles of maqāṣid al-sharī‘ah, particularly in safeguarding human dignity (ḥifẓ al-‘irḍ) and property (ḥifẓ al-māl). The Qur’an emphasizes that humans should not turn suffering into a form of entertainment, as warned in Q.S. Al-Ḥadīd [57]:20 concerning the delusions of the world (ghurūr ad-dunyā). Therefore, this study highlights the importance of applying Qur’anic social ethics in the digital space to foster moral awareness, social solidarity, and the dignified use of technology.